National libraries as centers of innovation: An IFLA Journal 40th anniversary tribute - Jerry W. Mansfield
IFLA Journal is an international journal publishing peer reviewed articles on library and information services and the social, political and economic issues that impact access to information through libraries. The Journal publishes research, case studies and essays that reflect the broad spectrum of the profession internationally.